Analyzing Gender and Location Disparities in Burnout among Secondary Students in Punjab: A Quantitative Investigation - Hijazi, Bushra; Iqbal, Muhammad Zafar; Shams, Jahan Ara (Annals of Human and Social Sciences, 2023)
This quantitative study examines secondary students’ burnout levels in Punjabi schools, highlighting variations based on gender and geography. The inquiry was directed by two main research questions: first, how much of a significant link there is between male and female students’ degrees of burnout, and second, how different rural and urban students’ levels of burnout in Punjab’s secondary schools are examined. Different patterns of burnout were found for different genders and geographical areas. In comparison to their female peers, male students had greater levels of Cynicism (CY) and Emotional Exhaustion (EME). On the other hand, women had far more Academic Efficacy (AE) burnout. These results are consistent with the general public’s opinion that female students are more conscientious and well-organized in their academic endeavours. Geographically speaking, students in rural areas demonstrated higher levels of EME and CY burnout than students in urban areas. Concerning geography, rural students showcased heightened levels of EME and CY burnout, while urban students reported elevated AE burnout. This discrepancy is attributed to better study resources and parental involvement in urban areas due to higher literacy rates. These outcomes underscore the impact of socio-environmental factors on student burnout, emphasizing disparities in educational support and resource availability between rural and urban settings. This research contributes valuable insights into understanding and addressing burnout among secondary students, aiding in the formulation of targeted interventions and support mechanisms.